Retirement decisions of people with disabilities: Voluntary or involuntary - Margaret Denton; Jennifer Plenderleith; James Chowhan (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2010)
While some retirement is welcomed and on-time, other retirements are involuntary or forced due to the loss of a job, an early retirement incentive, a health problem, mandatory retirement, lack of control with too many job strains, or to provide care to a family member. An analysis of the 2002 Canadian General Social Survey reveals that 27% of retirees retired involuntarily. This research focuses on the disabled population in Canada and considers factors that influence voluntary and involuntary retirement. Further, consideration is given to the economic consequences of retiring involuntarily. This research will examine issues surrounding retirement and disability through statistical analysis of the Canadian Participation and Activity Limitations Survey (PALS) 2006 data. Methods include the use of descriptive statistics and logistic regression analysis to determine the characteristics associated with involuntary retirement. This study found that those who retired involuntarily were more likely to have the following socio-demographic and socio-economic characteristics: age 55 or less, less than high school education, live in Quebec, rent their home, and have relatively low income. They were also more likely to be worse off financially after retirement and to be receiving social assistance or a disability benefit. In terms of disability, the likelihood of retiring involuntarily was greater for those with poor health at retirement, the age of onset was over 55, higher level of severity, and multiple types of disability. For the discussion, a social inequalities framework is used, where health selection into involuntary retirement depends on social location defined by age and education. Policy initiatives that reduce the effects of disability, and allow individuals to remain in or return to the labour force such as workplace accommodations are discussed.
Keywords: J14; 330; retirement; disabled; health; labour force; Arbeitsbedingungen; Altersgrenze; Flexible Altersgrenze; Arbeitslosigkeit; Gesundheit; Kanada